Flexural buckling behaviour and resistances of circular high strength concrete-filled stainless steel tube columns - He, An (2022)
The flexural buckling behaviour and resistances of circular high strength concrete-filled stainless steel tube (HCFSST) columns were examined based on experiments and numerical modelling, and reported in the present paper. The experimental programme was conducted on 12 circular HCFSST columns with various member relative slendernesses, and included material tests, initial global geometric imperfection measurements and pin-ended column tests, with their procedures and setups fully described. The experimentally observed results, including the failure loads and modes as well as the load-deformation curves (load-end shortening curves and load-mid-height lateral deflection curves) of the circular HCFSST column specimens and the development of the longitudinal strains of the outer stainless steel tubes, were presented and discussed. The experimental programme was then supplemented by a numerical modelling programme, where finite element models were developed and validated against the test results, and then used for conducting parametric studies to generate further numerical data on circular HCFSST columns over a broad spectrum of cross-section dimensions and member lengths. Owing to the lack of international design codes for stainless steel–high strength concrete composite structures, the relevant codified design rules for circular normal strength concrete-filled carbon steel tube columns failing by flexural buckling, as used in Europe, America and Australia/New Zealand, were assessed for their applicability to circular HCFSST columns, based on the obtained experimental and numerical data. The assessment results indicated that the design rules, as given in the Australian/New Zealand standard and American specification, lead to many unsafe flexural buckling resistance predictions when used for circular HCFSST columns, while the design rules, as adopted in the European code, result in more safe and reliable design resistances for circular HCFSST columns failing by flexural buckling.